Emerging delivery platforms for Oro-mucosal administration of biopharmaceuticals: a critical update (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
Sometimes drugs are injected straight into veins. This is known as Intravenous administration. The medication reaches the blood supply directly in this scheme, eliminating any chemical, physical, or biological barriers. Since the absorption of the drug is guaranteed and immediate, IV administration is the best route for emergency situations. Furthermore, this technique allows highly exact controls over the dose and pace of administration, making it the optimal solution for medications that need a strict dosing regimen. On the other side, the IV method has risks of infection from the injection site caused by the needle such as phlebitis, thrombosis, and circulatory overload. Intravenous administration is a common method for delivering biopharmaceuticals. Because the bioavailability of the medicine administered via IV is theoretically 100%, making this approach performs better than other delivery routes. However, it should be noted that IV administration is not the ideal route for the delivery of vaccines. This is due to the difficulties associated with inducing effective immune responses via IV administration since the IV route does not provide an adequate local depot of antigens to stimulate/activate the innate immune response and induce the long-term secretion of antibodies. As a great alternative, oro-mucosal drug delivery systems have advanced, and their importance has been growing vastly and used in clinical settings. This review summarizes them over the intravenous delivery system.